Case Report: Laparoscopic Isthmocele Repair on an 8 Weeks Pregnant Uterus - Pirtea, Laurentiu; Balint, Oana; Secoşan, Cristina; Grigoraş, Dorin; Pirtea, Paul (Frontiers in Medicine, 2022)
An isthmocele, also known as a caesarean scar defect, is a long-term complication of caesarean sections with an increasing incidence. Although is often asymptomatic, it is a novel recognised cause of abnormal uterine bleeding, and it is a major risk factor for caesarean scar pregnancies or uterine ruptures in subsequent pregnancies. Currently there are no guidelines for the diagnosis and management of this condition. Several surgical techniques for the correction of isthmocele are proposed, including laparoscopic excision, vaginal repair, a combined laparoscopic-vaginal approach or more recently hysteroscopic resection. We present the case of a GII PI, 29 years old patient with a previous c-section who presented in our clinic with a positive pregnancy test for pregnancy confirmation. The ultrasound examination revealed an intrauterine evolutive 8 weeks pregnancy and a caesarean scar defect. After counselling the patient opted for pregnancy continuation and laparoscopic correction of the isthmocele. The surgery was performed under ultrasound guidance. The defect was resected, and the uterus was closed with a continuous two-layer suture. No intraoperative or postoperative complications were present. The pregnancy continued uneventfully A caesarean section was performed at term revealing a fully healed scar.